Case report: Rupture of an ileus tube in a patient with recurrent rectal cancer - Ma, Jun; Jiang, Ye; Zhou, Chaoping; Wang, Datian; Zhao, Chunxia; Zhang, Yaming (Frontiers in Oncology, 2023)
The insertion of an ileus tube is an important treatment for intestinal obstruction. According to previous reports, jejunal intussusception has been reported as a complication associated with ileus tube placement. However, rupture of the weighted tip of an ileus tube has not been reported before. Herein, we report a 55-year-old Chinese woman who underwent radical proctectomy (DIXON) for rectal cancer and developed pelvic recurrence and lung metastasis 65 months after surgery, accompanied by symptoms of acute intestinal obstruction. An ileus tube was inserted before the operation (extensive total hysterectomy, bilateral adnexal resection, rectal Hartman operation, partial enterectomy, and intestinal adhesion lysis). Rupture of the ileus tube occurred after the operation and was treated with paraffin oil and enteral nutrition, and the metal beads and spring were eliminated through the colostomy. During the follow-up, the patient received targeted therapy plus immunotherapy, which was successful: the quality of life of the patient was excellent, and no obvious abnormal symptoms were found. Endoscopy-assisted ileus tube insertion should be performed under intravenous anesthesia, and a knot should be tied at the tip of the ileus tube before insertion so that the ileus tube can be inserted easily by grasping the thread with biopsy forceps(the “thread-knotting” method). With the above methods, the procedure of ileus tube insertion could be improved to reduce the incidence of tube-related rupture.